Evaluation of Promising Sweet potato Clones for Higher Root Yield and Dry Matter Content - Rahajeng, Wiwit; Restuono, Joko; Indriani, Febria Cahya; Purwono, Purwono (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2021)
Dry matter content is one of the important characteristics of sweet potatoes in addition to high yield. The aim of this study was to evaluate the performance of promising sweet potato clones for higher root yield and dry matter content. A hundred promising sweet potato clones were evaluated and arranged in randomized block design with two replication. The variables observed included: weight of vine, harvest index, number of root per plot, the weight of root per plot, dry matter content, root yield, root skin color, and flesh color. The analysis of variance showed a significant difference among the tested genotypes in all traits observed. A hundred promising sweet potato clones showed that root yield has varied ranged from 4.88–41.38 t h-1 with an average 20.28 t h-1 and dry matter content ranged from 19.19 – 40.65% with an average 30.47%. Fifteen promising clones of a hundred clones tested had high root yield and dry matter content with varying color flesh.